W poszukiwaniu muzycznej topiki karnawałowej. „Karnawały”orkiestrowe z lat 1913–1945 - Rusin, Anna (Res Facta Nova, 2025)
The article aims to analyze the orchestral “carnivals” composed between 1913–45 in the scope of Mikhail Bakhtin’s carnivalization and topic theory (introduced by Leonard Ratner) recently contributed by Joan Grimalt. To start with, the origins of orchestral pieces entitled“carnival” are outlined, regarding the traditions of Strauss dynasty and Hector Berlioz. Secondly, applying paradigmatic approach, the main tendencies are presented (carnival with or without fete, modern or old-fashioned carnival, home or foreign carnival, carnival based on owned or borrowed melodic material and film or incidental music) as well as the main genre types (fantasia, suite) within the pieces by composers of different nations (Antun Dobronić, Oskar Morawetz, Nikolay Ivanovich Kazanli, Heitor Villa-Lobos, Benjamin Britten, Emil von Rezniček, Aleksander Tansman, Darius Milhaud). As a result, the unique universe of topics emerges, establishing the specific relationships with reference to Greimas’s semiotic square, that can be understood as musical carnivalesque topica.